A model of Malaysian food image components: towards building a sustainable tourism product - Leong, Quee Ling; Othman, Mohhidin; Mohd Adzahan, Noranizan; Abdul Karim, Muhammad Shahrim (Universiti Putra Malaysia Press, 2012)
Food is becoming an important or a critical motivating factor for travellers when choosing a destination. Past scholars found that images could trigger imagination besides being a worthy basis for marketing strategy. Therefore, it is absolutely imperative to identify the food characteristics that form images prior to promoting and selling of the local food so as to draw more tourists to the country. Given the fact that a limited literature has been found on exploring food images in Malaysia, an attempt to conduct an exploratory research was therefore made. This study aimed at determining the definitions of Malaysian food, as well as the characteristics and types of food that best depict Malaysian gastronomy culture. Four focus groups were conducted, and these consisted of general public and practitioners from the food industry in Malaysia. The data were then verbatim transcribed and analysed using a coding system. The information obtained from this study is anticipated to assist marketers in developing a comprehensive strategic marketing plan that focuses on targeting food tourists. The paper ends with feasible enforcements suggested to assist catalysing growth in the food tourism industry in Malaysia.